Access and success in higher education: Disadvantaged students’ lived experiences beyond funding hurdles at a Metropolitan South African university - Chiramba, O.; Ndofirepi, E. S. (South African Journal of Higher Education, 2023)
In the context of South Africa’s complex historical legacy of inequality, access to higher education and academic success have become pressing concerns for governments, institutions, and scholars globally. While strides have been made post-1994 in South African higher education, with increased enrollment and opportunities, disparities persist, particularly for marginalized communities in impoverished or rural areas. The study aims to contribute to the discourse on creating a fairer and more inclusive South African higher education system, offering insights that could reshape the understanding of funding challenges and inform potential solutions. The article used the qualitative empirical data of the Council on Higher Education project to understand the challenges faced by students from these backgrounds as they seek higher education, focusing on their lived experiences beyond financial obstacles. The theory of resilience is deployed to understand how they succeed despite the odds. The COVID-19 pandemic has exacerbated these challenges. The findings indicate that students from disadvantaged backgrounds face various funding challenges, and they strive to succeed despite the odds. The article advocates for institutions to teach as well as boost resilience to these students. Also incorporating the voices of disadvantaged students in debates about higher education funding can inform more inclusive and supportive educational environments. We also advocate for institutional resilience in sourcing more funding for this group.